2014
DOI: 10.9790/3008-09322327
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of in vivo interactions of binary mixtures of salts of metals in alcoholic milieu on the liver and kidney of male albino Westar rats

Abstract: Effects of alcoholic solution of binary mixtures of salts of metals on some hepatic and nephrotic parameters in animal model was monitored using spectrophotometric technique. The serum activities of ALT, AST, ALP and concentrations of ALB, TP, UR, CR were assayed. Animals were orally exposed to the solutions continually for seven, fourteen and twenty one consecutive days respectively. Results obtained showed increased activities of ALT particularly for groups fed Fe+Zn and Pb+Fe relative control (P<0.01) where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Even though alcohol is toxic, its toxicity is increased in the presence of heavy metal salts (Gazuwa et al, 2006). Gazuwa et al (2014) reported that, in alcoholic environment, cadmium and lead salts elevated serum activities of AST, and ALP; also, the levels of UR and CR. Ethanol, due to its amphiphilic property is able to diffuse into all tissues and affect their vital functions (Lieber, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though alcohol is toxic, its toxicity is increased in the presence of heavy metal salts (Gazuwa et al, 2006). Gazuwa et al (2014) reported that, in alcoholic environment, cadmium and lead salts elevated serum activities of AST, and ALP; also, the levels of UR and CR. Ethanol, due to its amphiphilic property is able to diffuse into all tissues and affect their vital functions (Lieber, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, binary mixtures of salts of these metals in alcohol appear to enhance its toxicity on hepatic biochemical parameters. On nephrotic parameters Cd and Pb salts in alcohol caused a very significant increase in the level of serum urea (Gazuwa et al, 2014;Gazuwa et al, 2012). Cadmium and alcohol are toxic to cells and their co-administration has been reported to cause urinary protein excretion (Gazuwa et al, 2014); also, coadministration with iron and cadmium salts caused increase the level of serum creatinine (Gazuwa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation